Effect of paleopolyploidy and allopolyploidy on gene expression in banana - Cenci, A.; Hueber, Y.; Zorrilla-Fontanesi, Yasmín; Wesemael, Jelle van; Kissel, E.; Gislard, M.; Sardos, J.; Swennen, Rony L.; Roux, N.; Carpentier, Sebastien C.; Rouard, M. (Springer, 2019)
Bananas (Musa spp.) are an important crop worldwide. Most modern cultivars resulted from a complex polyploidization history that comprised three whole genome duplications (WGDs) shaping the haploid Musa genome, followed by inter- and intra-specific crosses between Musa acuminata and M. balbisiana (A and B genome, respectively). Unresolved hybridizations finally led to banana diversification into several autotriploid (AAA) and allotriploid cultivars (AAB and ABB). Using transcriptomic data, we investigated the impact of the genome structure on gene expression patterns in roots of 12 different triploid genotypes covering AAA, AAB and ABB subgenome constitutions.